Decision aids that really promote shared decision making: the pace quickens. (10th February 2015) - Agoritsas, Thomas; Heen, Anja Fog; Brandt, Linn; Alonso-Coello, Pablo; Kristiansen, Annette; Akl, Elie A; Neumann, Ignacio; Tikkinen, Kari AO; Weijden, Trudy van der; Elwyn, Glyn; Montori, Victor M; Guyatt, Gordon H; et al.
Abstract : Decision aids can help shared decision making, but most have been hard to produce, onerous to update, and are not being used widely. Thomas Agoritsas and colleagues explore why and describe a new electronic model that holds promise of being more useful for clinicians and patients to use together at the point of care